The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/j.2161-1939.2007.tb00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Counselor Wellness and Impairment: A National Survey

Abstract: Counselor wellness has a direct impact on the quality of services clients receive, but little is known about the overall wellness of counselors. This study begins the process of better understanding counselor wellness by examining responses to a national survey that assessed both counselor wellness and impairment variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
128
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(138 citation statements)
references
References 17 publications
(21 reference statements)
9
128
1
Order By: Relevance
“…Smith, Robinson, and Young (2007) also detected that the overall wellness of counselors in training was affected by their increased exposure to psychological distress. A recent national survey of American counselors corroborated this contention and indicated that a substantial number of counselors are at risk for burnout, compassion fatigue, and vicarious trauma at any given time (Lawson, 2007). The results of these authors' inquiries suggested that counselors in training are not only at greater risk for psychological distress, but that associated impairments may carry over into their careers.…”
Section: The Need For a Wellness Model Of Supervisionmentioning
confidence: 63%
“…Smith, Robinson, and Young (2007) also detected that the overall wellness of counselors in training was affected by their increased exposure to psychological distress. A recent national survey of American counselors corroborated this contention and indicated that a substantial number of counselors are at risk for burnout, compassion fatigue, and vicarious trauma at any given time (Lawson, 2007). The results of these authors' inquiries suggested that counselors in training are not only at greater risk for psychological distress, but that associated impairments may carry over into their careers.…”
Section: The Need For a Wellness Model Of Supervisionmentioning
confidence: 63%
“…Some authors (Goodyear, Bunch, & Claiborn, 2005;Shulman, 2005) have regarded clinical supervision as constituting the signature pedagogy of the counseling profession; others suggested that this supportive, developmental context may promote meeting CACREP and ACA requirements for general wellness practices and increase resilience among students (Lawson, 2007;Lenz & Smith, 2010;Meyer & Ponton, 2006). The imperative for focusing on personal wellness is indicated in the abundant accounts of vicarious trauma and compassion fatigue being addressed during supervision (Bober & Regehr, 2006;Harrison & Westwood, 2009;Hesse, 2002;Trippany, Kress, & Wilcoxon, 2004).…”
Section: Wellness Within Counseling Supervisionmentioning
confidence: 93%
“…When counseling students and counselors do not participate in a healthy lifestyle that promotes balance and optimum wellness, their ability to effectively facilitate the therapeutic relationship is compromised (Lawson, 2007;Smith et al, 2007). Although individuals have a certain amount of endurance for persisting and acclimating to stressors, when this threshold is surpassed, professional effectiveness and personal wellness may be compromised.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Implementing self-care strategies affords many benefits to new counsellors with studies generally showing that self-care can reduce distress and impairment, improve counsellor well-being, and help with retention in the counselling profession (Evans & Payne, 2008;Richards, Campenni, & Muse-Burke, 2010). Moreover, engaging in self-care practices that build insight may help new counsellors become more authentic in their practice which could allow them to provide higher quality care to clients while ensuring their own vitality (Lawson, 2007).…”
Section: Self-care Ethics and The Knowing-doing Gapmentioning
confidence: 99%